Targeting inflammatory cytokine storm to fight against COVID-19 associated severe complications - Hirawat, Rishabh (Life Sci, 2021)
Such testing and trying time probably never seen before in the human history. The novel coronavirus disease abbreviated as COVID-19 is the ongoing health crisis which entered into human life in late December 2019. The ease of transmission between humans and the undetectability in early stage makes COVID-19 frightening and unprecedented. The disease is characterised by pneumonia progressing to breathing difficulty, acute respiratory distress syndrome (ARDS) and multi-organ failure. Clinical studies suggest excessive release of inflammatory mediators leads to cytokine storm, a phenomenon which appears to be potentially life-threatening in COVID-19. Across the globe, when the world authorities are grappling to contain the virus, our review provides a glimpse on structure, pathophysiology of the virus and further sheds light on various clinical complications associated with the disease in order to open up/raise new horizons to explore various possible theoretical targets for COVID-19. The review also portrays a question and debates: Can targeting cytokine storm can be a feasible approach to combat COVID-19?